'Biracial'-Looking Twins: A New Twin Type?/Twin Research: Twins with Cystic Teratomas; Sleep Quality and Body Mass Index; Previable Membrane Rupture/Print and Online Reports: Twins Born to a Sister Surrogate; NASA Twin Study; African-Cosmopolitan Twin Fashion Inspirations; Triplet Hockey Stars. (June 2017) - Segal, Nancy L.
Abstract : Dizygotic (DZ) co-twins born to mothers and fathers from different racial or ethnic backgrounds often resemble one parent much more than the other. As such, these pairs comprise a unique subset of twins for investigating how others' responses to their different looks may affect their personalities and self-esteem. This article describes some of these twin pairs and some challenges of raising them, and suggests ways they may be used in research. Next, recent twin research on cystic teratomas, relations between sleep quality and body mass index, and previable membrane rupture is described. The final section concerns twins, twin studies, and related events in the media, namely: twins born to a sister surrogate, the NASA twin investigation, inspiring African-Cosmopolitan twins in fashion, and triplet Hockey Stars.